Effect of music on surgical hand disinfection: a video-based intervention study. Issue 4 (April 2017) - Gautschi, N.; Marschall, J.; Candinas, D.; Banz, V.M.
Summary: Surgical hand disinfection (SHD) is likely to be influenced by various factors. The aim of this study was to evaluate the effect of listening to music on the duration of SHD. In total, 236 SHD procedures were recorded on video. The duration of SHD exceeded 2 min in both the intervention group and the control group, with background music unable to achieve an increase in the time spent scrubbing. However, listening to music reduced the proportion of very short scrub times (<90 s) from 17% to 9% ( P  = 0.07). The following four factors increased mean scrub time significantly: female sex; lower staff seniority; scrubbing hands in groups; and use of a stopwatch. Although the improvement observed did not reach significance, it is suggested that background music may be useful for the 10% of healthcare workers who perform very short scrubs.